The End of the North-South Wage Differential: Reply - Coelho, Philip R. P.; Ghali, Moheb A. (American Economic Review, 1973)
In his comment, Mark Ladenson contends that substantial differences in wages still exist between the North and the South even after accounting for differences in regional prices. We find his results objectionable on three grounds: a) his arbitrary exclusion of available data, b) his choice of a low budget cost of living as a deflator, and c) the possibility of heteroscedasticity which would render his testing procedure invalid. Ladenson objects to four of the five cities we used as our southern sample, all previous empirical work notwithstanding. These five cities were used in our analysis because they were the only five cities for which the necessary 1963 data were available. Similarly, the five cities included in our Northeast sample were the only Standard Metropolitan Statistical Areas (SMSA) for which complete 1963 data existed.' If we consider 1967 data, there are many more SMSAs in both regions than are utilized by Ladenson. (Our data sources are identical to Ladenson's: Census of Manufacturers 1967 and Handbook of Labor Statistics 1970.) In this study we use all the data available by: 1) examining wage differentials throughout the entire United States, 2) offering alternative definitions for the Northeast and South, and 3) using different deflators to measure differentials in the regional cost-of-living. The statistical techniques used are similar to those employed by Ladenson and in our previous paper, p. 934, except that we have added two additional dummy variables to account for the additional geographical regions, the North Central and western regions of the United States. Dummy variables, then, exist for the South, North Central, and West of the United States; consequently we are comparing wages in these regions to wages in the Northeast.2 Industry 21 of the Standard Industrial Classification